Economic and Legal Problems of the Development of the Ukrainian Small Aviation Market and Ways to Solve Them - Pererva, P. G.; Kobielieva, T. O.; Glisnuza, M. Yu.; Ievsieieva, O.; Doronina, M. S.; Kosenko, A. V (Kaunas University of Technology, 2024)
A study of the Ukrainian market of small aircraft has been carried out. Specific segments of this market have been formed, which represent various areas of use of small aircraft in Ukraine and emphasize the many functions that can be performed by small aircraft in various sectors of the economy and society. The original characteristics of the small aircraft market are identified and substantiated. Among them: low payload, short and medium-haul operations, flexibility and accessibility, entertainment and business purposes, public services, development of unmanned technologies. It is substantiated that the market of small aircraft in Ukraine faces a number of problems that are due to various objective and subjective factors and affect its development. Among them, two groups of the most important problems are singled out: problems of economic and legal content. Among the economic problems, special attention is paid to the unstable economic and political situation in the country, which is caused by the war with Russia; insufficiently developed infrastructure of the small aircraft market; Certification and regulatory challenges, and high operating and maintenance costs. Among the legal problems, the authors highlight high customs and state duties; non-compliance with international norms and standards of small aircraft; low level of justification of taxation, excise taxes, environmental protection and waste management standards. Particular attention is paid to the need to improve flight rules, standards and requirements for pilot qualifications. The research and analysis of the current state of the Ukrainian market of small aircraft has become the basis for highlighting a number of problematic tasks that require immediate economic, regulatory and legal solutions. Such tasks in the report include the following: legal legalization of small aircraft in Ukraine; regulatory and legal use of airspace; organization and control of air traffic; information support of small aircraft flights; certification of small aircraft; peculiarities of obtaining rights to operate small aircraft; Maintenance of lethal means. For each of these tasks, an economic and legal mechanism for their solution is presented, based on the capabilities of Ukraine in the current economic and political situation. As a direction for further research, it is proposed to conduct an economic and legal justification for the development of the processes of development, production and operation of unmanned small vehicles, which is of particular relevance for modern Ukraine.
Keywords: small aviation; Ukrainian market; analysis; research; economic problems; legal problems; characteristics; tasks; solutions; efficiency